BETWEEN PRINCIPLE AND PRACTICE: NEPAD AS AN INDICATOR OF AFRO-CENTRISM IN NIGERIAN FOREIGN POLICY - Solomon Tai Okajare (European Scientific Journal, ESJ, 2012)
Following the attainment of her independence in 1960, Nigeria was ushered in to an international system that was thoroughly split into two different ideological divisions. There were the Western bloc, led by the United States of America, with democracy and capitalism as its core politico-economic ideological persuasion, and the Eastern bloc, led by the defunct Soviet Union, which embraced communism and socialist drive. This ideological division made the emergent African states of the 1960s enmeshed in the vortex of power manipulations and vulnerabilities from these ideological Powers. This made it expedient for the African states to exert and assert their independence both in spirit and letters. It was against this backdrop that Nigeria opted for an Afro-centric foreign policy, which would enable her promote and protect pan-African interests within the international system. This paper situates the involvement of Nigeria in the NEPAD initiative as a critical effort in the process of maintaining and strengthening an Africa-centred foreign policy, by way of providing effective leadership for the Continent. We argue that the initiative was in the best strategic interests of Nigeria in view of her pivotal position in terms of core elements of power in the comity of African states.